2013
DOI: 10.1155/2013/396156
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Coprothermobacter proteolyticus Alkaline Serine Protease

Abstract: A putative protease gene (aprE) from the thermophilic bacterium Coprothermobacter proteolyticus was cloned and expressed in Bacillus subtilis. The enzyme was determined to be a serine protease based on inhibition by PMSF. Biochemical characterization demonstrated that the enzyme had optimal activity under alkaline conditions (pH 8–10). In addition, the enzyme had an elevated optimum temperature (60°C). The protease was also stable in the presence of many surfactants and oxidant. Thus, the C. proteolyticus prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For instance, Proteiniphilum , Clostridium, Anaerobaculum , Coperothermobacter , Azorcus, Gelria, Sporanaerobacter, Coprococcus. Caldicoprobacter, Tepidanaerobacter , Paracoccus, Syntrophomonas , Gordonia and Acidovorax were the dominant genera shared between pyrotags in the sludge, and appeared to be well‐adapted to the infrastructure environment of anaerobic digesters . Members of the genera Clostridium , Coprococcus and Caldicobacter exhibit various features that demonstrate their potential for fermentation of a wide range of organic compounds and VFAs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Proteiniphilum , Clostridium, Anaerobaculum , Coperothermobacter , Azorcus, Gelria, Sporanaerobacter, Coprococcus. Caldicoprobacter, Tepidanaerobacter , Paracoccus, Syntrophomonas , Gordonia and Acidovorax were the dominant genera shared between pyrotags in the sludge, and appeared to be well‐adapted to the infrastructure environment of anaerobic digesters . Members of the genera Clostridium , Coprococcus and Caldicobacter exhibit various features that demonstrate their potential for fermentation of a wide range of organic compounds and VFAs .…”
Section: Discussionmentioning
confidence: 99%
“…Caldicoprobacter, Tepidanaerobacter, Paracoccus, Syntrophomonas, Gordonia and Acidovorax were the dominant genera shared between pyrotags in the sludge, and appeared to be well-adapted to the infrastructure environment of anaerobic digesters. 23,60,63,64 Members of the genera Clostridium, Coprococcus and Caldicobacter exhibit various features that demonstrate their potential for fermentation of a wide range of organic compounds and VFAs. 57,60,63 Members of Coperothermobacter (Firmicutes) and Proteiniphilum (Bacteriodetes) are known as proteolytic bacteria, able to hydrolyze proteins to amino acids with proteases, and degrade amino acids to VFAs and NH 4 + N. 63,64 Gelria are strictly anaerobic, moderately thermophilic and obligately syntrophic, and play an important role in H 2 transfer to the methanogenic partners.…”
Section: Bacterial Taxonomic Genera In Sludge Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter finding is in line with many previous studies where Coprothermobacter and Methanothermobacter were found to live in strict syntrophic associations (Sasaki et al 2011;Ge et al 2012). Proteolytic activity of Coprothermobacter is well documented (Etchebehere et al 1998;Tandishabo et al 2012;Majeed et al 2013;Lü et al 2014), and in particular this microorganism is capable to ferment proteins, growing well in presence of peptides (Ollivier et al 1985). Therefore, the solubilization of proteins into small molecules can promote Coprothermobacter establishment, especially at high temperatures (Lee et al 2009).…”
Section: Thermophilic Microbial Communitymentioning
confidence: 99%